Quantitative Analysis of Mycoflora and Aflatoxins in Green Coffee Beans from Sana'a, Yemen - Al Zubairy, Maysoon Abdulrahman; Moawad, Nada Abdullah; Al-Akhali, Basem (PSM Microbiology, 2025)
Coffee is one of Yemen’s most significant agricultural commodities, renowned since antiquity for its superior quality and distinctive flavor. In light of its economic and cultural importance, this study investigated fungal contamination in green coffee beans and quantified their aflatoxins content. Twenty samples were collected from retail outlets across Sana'a and analyzed for mycoflora using the agar plate method. All samples showed contamination with filamentous fungi. Fungal loads ranged from 20 CFU/40 beans (Sample 10) to 137 CFU/40 beans (Sample 4). The genus Aspergillus was predominant (71.84% of isolates), followed by Rhizopus (18.59%) and Penicillium (9.55%). Among Aspergillus species, A. niger was most frequent (518 CFU/40 beans; 33.68%; frequency: 95%), followed by A. melleus (185 CFU/40 beans; 12.03%; frequency: 80%) and A. aculeatus (166 CFU/40 beans; 10.79%; frequency: 65%). Total aflatoxins levels, determined using the AgraQuant Aflatoxins ELISA Test Kit, were detected in all samples, ranging from 17.61 ppb (Sample 19) to 23.34 ppb (Sample 9). These findings highlight the need for monitoring these under-investigated products and the establishment of regulatory oversight in the dietary supplement industry, particularly for botanical-based products such as green coffee.